Analysis of prospective physics teacher misconceptions about friction force with three tier tests and clinical interviews - Ahmad Busyairi; Muhammad Zuhdi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
A good and correct understanding of concepts is a fundamental thing that prospective Physics teachers must have before graduated from college. Therefore, it is necessary to identify the conception to ensure that there are no students who have misconceptions and do not understand the concept. This study aims at identifying the misconceptions experienced by prospective Physics teachers at the final level, especially in the friction force material. This is descriptive research conducted in a university in Mataram with 12 students involved. The instrument used was a three-tier test in the form of a multiple-choice test with open reasons. A total of 10 items with 30 questions were used in this study. Data collection techniques used was tests and interviews. The data that has been collected was then analyzed using descriptive statistics. Based on the results of the data analysis, it was found that 46.29% of the students had misconceptions with details of 50.00% of the students experienced misconceptions in determining the type of friction force, 43.75% in determining the direction of friction force, and 47.22% in determining the magnitude of the friction force. The results of this study indicate that there are still many students of prospective Physics teachers have misconceptions. Therefore, we need an alternative learning that can be used to reduce the misconceptions had by prospective Physics teachers.